Design and Simulation of Modular Multilevel Converter Fed Induction Motor Drive - Ahmed Kamil Hannan; Turki K Hassan (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
Traditional modular multilevel converter (MMC) applications in medium voltage induction motor drive are difficult, particularly at low speeds because of the higher magnitude of the voltage ripple of the sub-module capacitor. This paper uses a hybrid MMC, particularly at low frequencies, to achieve a lower peak-to-peak voltage ripple of the sub-module capacitor. The vector control strategy with the closed-loop speed control indicates an accurate and wide-speed range. MATLAB / Simulink is used to simulate and obtain the simulation results of hybrid and traditional MMC with induction motor drive and compare from the standpoint of capacitor voltage ripple. The results are shown the reduction of peak-to-peak voltage ripple of the sub-module capacitor as the hybrid MMC is operated.